2021
DOI: 10.7759/cureus.19689
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Drug Induced Acute Kidney Injury in Pediatric Intensive Care Unit

Abstract: Background: Acute kidney injury (AKI) is known to complicate one-third of cases in pediatric intensive care units (PICU), and almost one-fourth of these are due to nephrotoxic drugs (NTDs). Although stopping NTDs seems the most obvious option, it is not practically applicable. Many NTDs are the only existing option, and their potential benefits outweigh the risk of drug-induced AKI. Objectives: To assess the proportion of children receiving NTDs in the PICU and highlight the children who developed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, these in-hospital events can be attributed to the disease course, development of cytokine release storm, [ 33 ] or drug-induced renal injury related to COVID-19 therapy. [ 34 ] Despite this aspect could not be covered by our analysis, concomitant liver injury influencing AKI is another contributory event that can be attributed to multi-organ failure associated with COVID-19. The same findings were reproduced by a large single-center Iranian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these in-hospital events can be attributed to the disease course, development of cytokine release storm, [ 33 ] or drug-induced renal injury related to COVID-19 therapy. [ 34 ] Despite this aspect could not be covered by our analysis, concomitant liver injury influencing AKI is another contributory event that can be attributed to multi-organ failure associated with COVID-19. The same findings were reproduced by a large single-center Iranian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the development of kidney injury is related to medications in approximately 25% of critically ill children [ 17 , 18 , 19 ]. Gowa et al’s [ 20 ] study, which included 99 children in a PICU, reported that 97.9% of the patients were exposed to nephrotoxic drugs, and 46.5% of the patients developed drug-induced AKI. In our study, the rates of medications that are common in PICUs were found to be significantly higher in patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…3 Importantly, drugs are also a frequent cause of AKI in the pediatric intensive care unit. 4 Cyclosporin (CsA) is a dominant immunosuppressive drug utilized to prevent rejection following organ transplantation. 5 Despite its positive effect, the side effects of the CsA cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%